PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA MANAJEMEN PEMASARAN CV SEKAR SARI FLORIST KAYOON SURABAYA - KHARIZA, FILIA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
Customer relationship management or commonly known as CRM is one part of the marketing management. CRM really need to be applied by the company in order to maintain good relations with customers, and with the implementation of CRM, the customer is expected to have satisfaction, loyalty and doing repeated buying. CRM will be very effective if done by all parts of the company. The main target of CRM is to improve long-term growth and profitability of the company. In applying and developing CRM strategies, need five steps, namely: customer portfolio analysis, relationships with customers, network development, plan development value, and manage the customer life cycle.